2021
DOI: 10.3390/ijerph18073784
|View full text |Cite
|
Sign up to set email alerts
|

Planned Home Birth in Low-Risk Pregnancies in Spain: A Descriptive Study

Abstract: Previous studies have shown that planned home birth in low-risk pregnancies is a generally safe option. However nowadays, only 0.5 percent of deliveries have been at home in Spain. This study sought to understand the characteristics of planned home births with qualified healthcare professionals in low-risk pregnancies and their results on maternal and neonatal health in the Balearic Islands. The study followed a retrospective descriptive design to investigate planned home births from 1989 to 2019 (n = 820). So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 34 publications
5
24
1
1
Order By: Relevance
“…Nonetheless, the safety and risks related to home birth is not well expounded upon and is very much a topic of debate. Available published literature also substantiates regional variability (15,28,41,42,45,46,51).…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Nonetheless, the safety and risks related to home birth is not well expounded upon and is very much a topic of debate. Available published literature also substantiates regional variability (15,28,41,42,45,46,51).…”
Section: Discussionsupporting
confidence: 58%
“…Distinctly, our study has shown the majority (64.3%) of low-risk multiparous females experienced spontaneous deliveries at home and were less likely to undergo an operative birth (p<.001). A study originating from four Nordic countries in northern Europe have shown the majority of low-risk multiparous females who experienced spontaneous birth in their previous pregnancies were more likely to give birth at home (41), and low-risk pregnancies attended by quali ed midwives ushered in positive results among both maternal and newborn health levels, including low rates of obstetric intervention (28,42,43), similar to the investigation by Galera-Barbero & Aguilera-Manrique (15).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Outside of Hungary, several countries are considering the reintroduction of homebirths. This is based on claims of equal safety at lower intervention rates, compared to institutional births in which overtreatment may be present [ 19 ]. Furthermore, psycho-social advantages associated with homebirth for the mother are also beneficial [ 20 ] and the introduction of effective interprofessional collaboration should be driven for a safe home birth [ 21 ].…”
Section: Introductionmentioning
confidence: 99%